2021
DOI: 10.1002/mds.28777
|View full text |Cite
|
Sign up to set email alerts
|

Mild Parkinsonian Signs: A Systematic Review of Clinical, Imaging, and Pathological Associations

Abstract: A BS TRACT: Mild parkinsonian signs (MPS) have been widely studied during the past 3 decades and proposed as a risk marker for neurodegenerative disease. This systematic review explores the epidemiology, clinical and prognostic associations, radiological features, and pathological findings associated with MPS in older adults free from neurodegenerative disease. We find that MPS as currently defined are strongly associated with increasing age and increased risk of development of Parkinson's disease (PD), all-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 111 publications
(421 reference statements)
3
17
0
Order By: Relevance
“…The wearable motion sensor allowed us to obtain a more objective assessment of motor symptoms in PD, and a breakdown of the upper limb bradykinesia score into a rating of the speed, amplitude, and rhythm of the movements (Table 1). A recent review paper of mild parkinsonian signs suggested that mild motor changes in the elderly population in the form of a slightly higher MDS-UPDRS-III score in the absence of comorbidities could be an indicator of an increased risk for PD [69]. The mean total MDS-UPDRS-III score for our control cohort was 2.29 points.…”
Section: Discussionmentioning
confidence: 76%
“…The wearable motion sensor allowed us to obtain a more objective assessment of motor symptoms in PD, and a breakdown of the upper limb bradykinesia score into a rating of the speed, amplitude, and rhythm of the movements (Table 1). A recent review paper of mild parkinsonian signs suggested that mild motor changes in the elderly population in the form of a slightly higher MDS-UPDRS-III score in the absence of comorbidities could be an indicator of an increased risk for PD [69]. The mean total MDS-UPDRS-III score for our control cohort was 2.29 points.…”
Section: Discussionmentioning
confidence: 76%
“…Apart from future risk of PD, SP has also been found to be associated with future dementia, particularly in the elderly population 2 and with cerebrovascular disease 26 . We adjusted for both factors in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Mild abnormalities in movement may be seen as part of normal aging and during the early stages of a number of neurodegenerative conditions, including Parkinson's disease (PD). 1,2 Different terms have been used to describe these signs including sub-threshold parkinsonism (SP), mild parkinsonian signs and soft or mild extrapyramidal signs. The progression of PD is gradual and slow.…”
Section: Introductionmentioning
confidence: 99%
“…As some patients already had mild motor symptoms 46 (two or more UPDRS III items with a score of 1 or an item with a score of 2 or higher), they might represent a later stage of the prodromal phase. 47 Another notable…”
Section: Discussionmentioning
confidence: 99%